Arbitration law of Czech republic : - Bellohlávek, Alexander J. (JurisNet, 2013)
A comprehensive review of the arbitration law and practice in the Czech Republic including: discussion of arbitration practice and procedure; an examination of the jurisdiction of the arbitral tribunal; the appointment of arbitrators including the challenge and replacement of arbitrators; an analysis of the various types of awards including a discussion on deliberations, agreements, settlements, and the costs of arbitration; a discussion on the amendment and challenge of awards including the liability of arbitrators; and, a review of the enforcement of domestic and foreign arbitration awards.